Hubungan Profil Manusia Digital dengan Pendidikan Agama Kristen - Nainggolan, Deklay; Supit, Sugijanti (Institut Agama Kristen Negeri Manado, 2023)
This research aims to determine the extent of the relationship between digital humans and PAK (Christian religious education). This research was conducted using the literature study method. The research results show that current and future technological advances are not scary. How humans can survive and adapt to technological advances depends on humans themselves. PAK should be a protector for Christians in the face of advances in digital technology that are ready to prey, but there is no need to make technological advances a scourge that must be shunned. Technological advances should be responded to well and used as a friend in PAK teaching.